(untitled) (Homoeopathy for All, 2026)
Hypothyroidism happens when the thyroid gland doesn’t make enough thyroid hormone. This condition also is called underactive thyroid. Since the main purpose of thyroid hormone is to “run the body’s metabolism”, it is understandable that people with this condition will have symptoms associated with a slow metabolism. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of underactive thyroid.